FTIR study of the impact of PC[60]BM on the photodegradation of the low band gap polymer PCPDTBT under O2 environment - Dettinger, Ulf; Egelhaaf, Hans-Joachim; Brabec, Christoph; Latteyer, Florian; Peisert, Heiko; Chasse, Thomas (Chemistry of Materials, 2015)
The photodegradation of the low band gap polymer poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b]dithiophene)-alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT) during irradiation under white light (AM 1.5 conditions) has been studied in pristine polymer films as well as in blend films with [6,6]-phenyl C61 butyric acid methyl ester (PC[60]BM). In order to gain insight into the degradation process, FTIR spectroscopy has been used to follow the evolution of different subunits of the polymer and to probe the chemical product formation. In contrast to other polymers, not the alkyl side chains but the π-conjugated system is preferentially oxidized during the first stages of degradation. Furthermore, it has been shown that the subunits of the polymer backbone are differently affected by the degradation. Blending the polymer with PC[60]BM leads to a significantly larger impact on the stability of the cyclopentadiene group compared to the benzene ring of the benzothiadiazole group.
Keywords: Engineering controlled terms: Blending; Butyric acid; Conjugated polymers; Energy gap; Fourier transform infrared spectroscopy; Polymers 2; 1; 3-Benzothiadiazole; Alkyl side chains; Cyclopentadiene groups; Degradation process; FTIR spectroscopy; Low bandgap polymers; Pi-conjugated system; Pristine polymers Engineering main heading: Polymer films